1988
DOI: 10.1016/s0022-5347(17)41848-9
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Model to Evaluate Inhibition of Bone Resorption Induced by Human Prostate Cancer Cells in Nude Mice

Abstract: A model system of human prostate carcinoma in nude mice for searching out a method to protect the bone from cancer cells is described, in which the transplanted human prostate cancer cells were inoculated subcutaneously over the calvaria in nude mice after the periosteum wa disrupted. The tumor induced osteolysis associated with osteoclast proliferation accompanied with reactive new bone formation. This osteolysis was evaluated by measuring the increased area of bone resorption by its reduced opacity to X-ray,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
2

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 20 publications
0
13
0
2
Order By: Relevance
“…However, while important gains in understanding the role of osteoclastic activity have been made for osteolytic tumors, the importance of osteoclastic activity in the development of prostate cancer skeletal metastatic lesions has received little attention because of their overall osteoblastic radiographic appearance. Yet, despite the radiographic appearance, it is clear from histological evidence that prostate cancer metastases form a heterogeneous mixture of osteolytic and osteoblastic lesions (2,(20)(21)(22)(23). In fact, histomorphometric analysis of metastatic lesions reveals that osteoblastic metastases form on trabecular bone at sites of previous osteoclastic resorption, suggesting that bone resorption is required for subsequent osteoblastic bone formation (2).…”
Section: Discussionmentioning
confidence: 99%
“…However, while important gains in understanding the role of osteoclastic activity have been made for osteolytic tumors, the importance of osteoclastic activity in the development of prostate cancer skeletal metastatic lesions has received little attention because of their overall osteoblastic radiographic appearance. Yet, despite the radiographic appearance, it is clear from histological evidence that prostate cancer metastases form a heterogeneous mixture of osteolytic and osteoblastic lesions (2,(20)(21)(22)(23). In fact, histomorphometric analysis of metastatic lesions reveals that osteoblastic metastases form on trabecular bone at sites of previous osteoclastic resorption, suggesting that bone resorption is required for subsequent osteoblastic bone formation (2).…”
Section: Discussionmentioning
confidence: 99%
“…29 Early animal work in the 1980s demonstrated that the bisphosphonates clodronate and etidronate inhibited tumour-mediated osteolysis induced by implanted prostate cancer cells. [30][31][32] A later exciting development came when in vitro work established that bisphosphonates also act directly on tumour cells themselves. They have been shown to inhibit cell proliferation and viability, and induce apoptosis in a number of cancer cell lines, including prostate cancer.…”
Section: Current Treatment Options For Bone Metastasesmentioning
confidence: 99%
“…With regard to experimental model systems of neoplasmassociated local osteolysis, tumour-bone interactions using calvaria of the mice were extensively studied by our group (Nemoto et al, 1986;Nemoto et al, 1987;Nemoto et al, 1988a;Nemoto et al, 1988b). In one of the recent studies, suggestive evidence was obtained that our system might be suitable for studying the biology of local interaction between bone and cancer cells.…”
mentioning
confidence: 89%
“…The method consisted of inoculating tumour cells subcutaneously (SC) (Fleisch et al, 1969;Fleisch & Felix, 1979;Fleisch, 1983). Inhibition of tumour induced osteolysis by bisphosphonates has been noted in animal and human studies (Jung et al, 1981; VanHoltenVerzantvoort et al, 1987;Morton & Howell, 1988).With regard to experimental model systems of neoplasmassociated local osteolysis, tumour-bone interactions using calvaria of the mice were extensively studied by our group (Nemoto et al, 1986; Nemoto et al, 1987;Nemoto et al, 1988a;Nemoto et al, 1988b). In one of the recent studies, suggestive evidence was obtained that our system might be suitable for studying the biology of local interaction between bone and cancer cells.…”
mentioning
confidence: 99%